Mediação de conflitos no contexto acadêmico: concepções, experiências e possibilidades - Conte, Laís Sincas (2020)
In recent times, probably due to phenomena that are related to social and political changes, there has been an increase in situations of tension in the academic universe. Universities are experiencing more and more conflicts and situations of exacerbated contradictions between the subjects who are members of academic communities. Concomitantly, in diverse environments, conflict mediation has gained ground as a tool that facilitates dialogue, allows collaborative understanding and transforms situations of divergence. Given that historically academic institutions have played an important role in building new perspectives of sociability and democracy, in reflecting on social crises and in proposing alternatives to face violence, prejudice and the threat to peace, it seems appropriate to analyze a tool based on dialogue to face conflicts within the academic environment. This work therefore seeks, in general, to understand conflict mediation in the academic environment to resolve disagreements that emerge from interpersonal relationships, aiming to generate opportunities for advances and the development of socio-emotional training, contributing to the maintenance of the university as a humanized, democratic space, that respects diversity. The study is based on the theoretical framework on conflict mediation addressed, among other authors, by Moore (1998), Warat (1998), Muller (2006), Muszkat (2008), Bertaso and Prado (2017) and Vasconcelos (2018). The problem that guides the research is: What are the possibilities of contribution of the mediation resource to treat, mitigate or transform the conflicts that occur in the academic context? The research presents a qualitative design and has an exploratory character. For the data collection, semi-structured interviews were employed in four sectors of a community university in the interior of Rio Grande do Sul, namely: the Pedagogical Support Center, the Student Attention Sector, the Ombudsman Office and the Institutional Evaluation Division. The data underwent qualitative analysis which demonstrated that many of the conflicts emerging in the academic context can be treated by conflict mediation. This conclusion was possible due to the realization of the need for external assistance for conflict resolution, the existence of a continued relationship between people, the manifestation of emotional issues, the existing communication noise, the existence of distortions in perceptions, as well as stereotypes that hinder productive exchanges. It was also evident that the university develops actions that value dialogue and is open to reflections and collective constructions, which could be further strengthened with the practice of conflict mediation.